Measuring Clinical Reasoning and Interprofessional Attitudes - Emily Johnson; Gretchen Seif; Patty Coker-Bolt; Sara Kraft (Journal of Student-Run Clinics, 2017)
Background: Interprofessional learning, collaboration and clinical reasoning are vital in medical education and medical care in order to best meet the needs of todayâ€™s patients.  Student-run free clinics are a type of learning experience that can foster interprofessionalism and develop clinical reasoning skills.  Ongoing evaluation of student attitudes, behaviors, and knowledge related to interprofessionalism and clinical reasoning are beneficial in order to continually improve education and curricula and maximize student learning outcomes. While numerous tools exist to measure student attitudes toward interprofessionalism and clinical reasoning skills, there is a lack of high quality measurement tools in this field. Methods: This study completed an exploratory factor analysis of the Self-Assessment of Clinical Reflection and Reasoning (SACRR) and the Interprofessional Education Scale (IEPS) to develop a new shortened interprofessional and clinical reasoning evaluation tool to measure student perceptions of interprofessionalism and clinical reasoning skills. Results: Factor analysis of SACRR yielded 4 factors, and RIPLS yielded 3 factors. In an overall exploratory factor analysis of SACRR and IEPS together, 11 significant factors emerged, with 5 of the factors having questions that loaded to them. Thirteen total questions loaded to each of the factors, forming the basis for a new survey tool.Conclusions: This new shortened survey tool can be beneficial to measuring interprofessional student learning outcomes and enhancing medical education, thereby improving the overall quality of health care delivery.